Effect of Nanobubble Air Pressure on the Hatching Success of Giant Gourami (Osphronemus gouramy) Eggs - Rio Yusufi Subhan; Kurnia Faturrohman; Nurul Fatimah; Maisuri Hardani; Linuwih Aluh Prastiti (Universitas Islam Lamongan, 2026)
Giant gourami (Osphronemus gouramy) is an important freshwater commodity in Indonesia, but seed production is often constrained by low egg hatching rates and poor larval survival. Optimizing dissolved oxygen during egg incubation is critical, particularly because embryos and early larvae have not yet developed functional accessory breathing organs. This study evaluated the effect of different nanobubble air pressures on the hatching performance of giant gourami eggs. A completely randomized design with four treatments and three replications was applied: A) incubation without nanobubble (control); B) nanobubble air pressure of 0.3 psi; C) 0.6 psi; and D) 0.9 psi. A total of 1,000 eggs per incubation basin were stocked in 12 basins, and nanobubble aeration was supplied using a high-blower pump, fine-bubble diffusers, and digital manometers. Observed parameters included fertilization rate, hatching rate, hatching time, survival rate until day 3, and basic water quality (dissolved oxygen, temperature, and pH). Nanobubble air pressure significantly affected hatching time and larval survival (p < 0.05), but had no significant effect on hatching rate (p > 0.05). The 0.6 psi treatment yielded the best biological performance, with fertilization rate of 91.57%, hatching rate of 83.53%, and survival rate of 94.58%, and along with the fastest hatching time (36 h 43 min at 80% hatch). Dissolved oxygen ranged from 4.36–5.75 mg L⁻¹, temperature 31.7–32.2°C, and pH 7.2–7.7 across treatments, all within acceptable ranges for gourami incubation, with the most stable conditions observed at 0.6 psi. These findings indicate that nanobubble aeration at 0.6 psi is an effective and practical strategy to improve egg hatching performance and early larval survival of giant gourami, and can be readily applied in small- to medium-scale hatchery systems with relatively low operational costs.